CONSTRAINTS, TO EFFECTIVE IMPLEMENTATION OF SECONDARY SCIENCE CURRICULUM IN NIGERIA - Matazu, Suleiman Sa’adu (Sokoto Educational Review, 2020)
The significance of science and technology for sustainable national development has created a very serious awareness on the need for science education. Numerous science curricula have been developed to help achieve the objectives of science education which depend on effective implementation of the science curriculum. This paper therefore discusses the various constraints to effective implementation of the curriculum which include voluminous content of curriculum, poor remuneration among others. Elimination of less relevant topics, giving good motivational incentives were recommended as some of the possible way out.